Ação leishmanicida de extratos de plantas no desenvolvimento de promastigotas de Leishmania amazonensis e estudo do perfil metabólico utilizando a técnica de cromatografia líquida de alta eficiência (CLAE). - MENDES, Josireny Mariano (2006)
Two million new cases of Leishmaniose occur annually in the tropical and subtropical areas of the globe, with a estimate of twelve million people currently infected in world and three hundred and fifty million under infection risk. The Leishmania sort, responsible for the disease, understands many diverse and complex species that present resistance to the drugs used in its treatment, beyond the characteristics undesirable. The effectiveness of the control and treatment of a parasitic disease depends on the detailed knowledge of the cycle of life, metabolism and biology in general of the parasite. The World Health Organization, associated with other agencies of research has stimulated the extract inquiry new of native plants as alternative for the treatment and combat of the parasitic disease In this work one standardized techniques of studies biochemists through liquid chromatography high performace (HPLC) evaluating organic acid excretion and consumption of in promastigotes of Leishmania amazonensis and became fullfilled biotests with Magonia pubescens (tingui) and Glycyrrhisa glabra (alcaçuz) in the concentrations of 25 50 and 100 mg.L-1 The acid had been detected following: lactate oxalate citrate -Ketoglutarate succinate fumarate malate and propionate demonstrated activities in the glycolytic pathway cycle of Krebs and respiratory chain Both the tested extracts had presented leishmanicid action with better effect for Glycyrrisa glabra 100 mg.L-1 and Magonia pubescens 25 mg.L-1 The Glycyrrisa glabra had better action in the stationary phase of growth to opposes it of Magonia pubescens that better acted in the logaritmic phase Chemical components of plants can act directly or indirectly in the metabolism of the parasite affecting essential metabolic pathways